International handbook on the economics of integration (Cheltenham Edward Elgar, 2011)
With this Handbook, Miroslav Jovanovi has provided readers with both an excellent stand-alone original reference book as well as an integral part of a comprehensive three-volume set. This introduction into a rich and expanding academic and practical world of international economic integration also provides a theoretical and analytical framework to the reader, presenting select analytical studies and encouraging further research. International Handbook on the Economics of Integration, Volume II covers three broad themes: competition, spatial location of economic activity and financial issues. With 20 chapters written by 34 eminent authors, this comprehensive Handbook begins by examining competition and industrial policies from a European perspective. It goes on to discuss the geography of production looking at the spatial (locational) effects of economic integration from various theoretical, regional and practical angles. The third and final part of the Handbook analyses monetary issues linked with economic integration at both the European and global level, as well as fiscal matters dealing with tax competition, taxation puzzles and a review of European experiences. Contributors to this major reference work include eminent authors, some of whom contributed to the creation of economic integration theory from the outset. The authors not only survey the literature, but also present their own arguments and new ideas in order to offer a new perspective, as well as discussing the issues they believe are essential in the field. Each of the insightful chapters is approachable not only to graduate students, scholars, researchers and policymakers, but also to advanced undergraduate students.
Includes bibliographical references and index.
Keywords: International economic integration